2004
DOI: 10.1002/art.20291
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic acid increases the severity of spontaneous knee osteoarthritis in a guinea pig model

Abstract: Objective. To determine whether ascorbic acid might be of benefit for the treatment of spontaneous osteoarthritis (OA) when administered over a long period of time.Methods. We investigated the effects of 8 months' exposure to low, medium, and high doses of ascorbic acid on the in vivo development of histologic knee OA in the male Hartley guinea pig. The low dose represented the minimum amount needed to prevent scurvy. The medium dose was the amount present in standard laboratory guinea pig chow and resulted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(51 citation statements)
references
References 40 publications
1
50
0
Order By: Relevance
“…Ascorbic acid (ASA) is a water soluble vitamin, acting as a cosubstrate for hydroxylase and oxygenase enzymes involved in the biosynthesis of pro-collagen, carnitine and neurotransmitters, which is necessary for the skin, cartilage and bone formation, growth, and reproduction (Darias et al, 2011;Kraus et al, 2004;Tolbert, 1979). ASA is also a powerful antioxidant which protects low density lipoproteins from oxidation, reduces harmful oxidants in the stomach and promotes iron absorption (Padayatty and Levine, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Ascorbic acid (ASA) is a water soluble vitamin, acting as a cosubstrate for hydroxylase and oxygenase enzymes involved in the biosynthesis of pro-collagen, carnitine and neurotransmitters, which is necessary for the skin, cartilage and bone formation, growth, and reproduction (Darias et al, 2011;Kraus et al, 2004;Tolbert, 1979). ASA is also a powerful antioxidant which protects low density lipoproteins from oxidation, reduces harmful oxidants in the stomach and promotes iron absorption (Padayatty and Levine, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Although this was a rigorous 6-month, double-blind placebo-controlled trial, study limitations (including trace amounts of selenium found in the placebo), as well as low power due to small sample size (n 30) should be considered. In contradiction to all other published findings, a 2004 study conducted on guinea pigs observed a dose-dependent, positive association between ascorbic acid supplementation and the severity of spontaneous OA (24) . In addition, Kraus et al (24) noted a correlation between the knee joint histological severity scores and plasma ascorbate concentration (r 5 0?38, P 5 0?01) and concluded that osteoarthritic patients should not consume above the Recommended Daily Value for vitamin C. The present study highlights the complexity of the relationship between the pathogenesis of OA and dietary antioxidant consumption and underscores the need for related, rigorous clinical research investigations.…”
Section: Discussionmentioning
confidence: 62%
“…Much focus has been put on this vitamin due to involvement in the biosynthesis of carnitine, neurotransmitters, and collagen (Terova et al 2001;Kraus et al 2004;Darias et al 2011), and ascorbic acid has also shown a specific role in mineral metabolism (Sandnes 1991), the stress response (Ren et al 2010), immunity (Waagbø 2006), and wound healing (Wahli et al 2003). Consequently, an appropriate amount of ascorbic acid should be supplied in fish feed from exogenous sources to ensure their normal growth and health (Pitaksong et al 2013).…”
mentioning
confidence: 97%